Factores de convivencia en parejas que presentan una permanencia en su relación por diez años o más: Un estudio en la ciudad de Santiago de Cali (2021)
The following investigation pretended to evaluate the factors of coexistence, among them the commitment, as mayor predictor of persistence or break-up in a group of couples that have a minimum of 10 years of cohabitation, and those couple live in Santiago de Cali, we are going to focus in 4 of these factors in particular measured by the Investment Model Scale which are satisfaction, quality of alternatives, investment size and commitment, which is a result of the latter factors. T